Analysis of water fertility status based on the Trophic State Index (TSI) in the Air Hitam Urban Polder, Samarinda Ulu District, East Kalimantan - Costarika, Stefhanie Stevi; Hamdhani, Hamdhani; Masruhim, Amir (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2025)
Waters near urban centers are highly vulnerable to pollution, a condition likely occurring in the Air Hitam Polder in Samarinda, which receives inflow from urban drainage and is surrounded by intense human activity. This study aimed to determine the Polder’s trophic status using the Carlson Trophic State Index (TSI) based on water transparency, total phosphate, and chlorophyll-a, analyzed spatially and temporally. It also assessed general water quality and examined the relationship between nutrients (phosphate, nitrate, ammonia) and chlorophyll-a. Measurements at five stations included transparency, chlorophyll-a, DO, EC, TDS, temperature, pH, and turbidity, with laboratory analyses for phosphate, nitrate, and ammonia. Sampling was conducted six times. Results show Station 3 had the highest TSI (75.25), likely due to its location near the main inlet carrying organic and inorganic materials. Temporally, the Polder was classified as hypereutrophic, with TSI values >60 at all stations. Phosphate had the strongest relationship with chlorophyll-a. Several parameters (DO, EC, TDS) met water quality standards, while others (phosphate, nitrate, ammonia, temperature, pH, transparency, turbidity) exceeded limits. Overall, current conditions are unsuitable for aquatic life, indicating the need for improved management to restore the ecological function of the Air Hitam Polder.